MINAT MEMBACA MAHASISWA PROGRAM STUDI PENDIDIKAN KESEJAHTERAAN KELUARGA DALAM PENULISAN SKRIPSI DI FAKULTAS PARIWISATA DAN PERHOTELAN - Nuraini, Nuraini; Syarif, Wirnelis; Elida, Elida (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The background of this research is not maximal thesis writing is measured from the time of completion of thesis students of the Faculty of Education of Family Welfare in Tourism and Hospitality, it is suspected because of the low reading interest of students of Education Studies Program of Family Welfare in the thesis. The purpose of this study was to describe the reading interests of students of Education Studies Program of Family Welfare in a thesis at the Faculty of Tourism and Hospitality. This type of research is descriptive quantitative. The study was conducted in the Department of Family Welfare. The population is students 150 person with a sample of 60 people were taken by random sampling technique. The data source is the students who have taken courses thesis.collecting using questionnaires (questionnaire) designed by Likert. scale data analysis was performed using SPSS version windows 19:00. The results of this study portray that (1) your reading interests of students of Education Studies Program of Family Welfare in a thesis at the Faculty of Tourism and Hospitality as a whole of 60 samples were included in both categories, (2) 2 (3%) of respondents expressed very well, ( 3) 44 (74%) respondents said that either, (4) 14 (23%) of respondents stated enough. Kata kunci: Interest, Family Welfare Education Students, Thesis